Tingkat Kerusakan Ekosistem Mangrove di Desa Teluk Belitung Kecamatan Merbau Kabupaten Kepulauan Meranti - UMAYAH, SARI; GUNAWAN, HARIS; ISDA, MAYTA NOVALIZA (Jurusan Biologi FMIPA Universitas Riau, 2016)
The destruction of mangrove forest ecosystems in Teluk Belitung Village, Kepulauan Meranti, wascaused by various human activities such as industrial activities, illegal logging, and coastal erosion.Rehabilitation efforts was needed to preserve mangrove forests. The community involvement had animportant role in determining the success of mangrove rehabilitation. This study aimed to determine theextent of mangrove forest ecosystem destruction based on the density and mangrove forest cover.Furthermore, this research described local community participation level and their knowledge inrehabilitation efforts of mangrove forest ecosystem. This study was conducted in Teluk Belitung,Subdistrict of Merbau, Kepulauan Meranti from November 2014 to March 2015. This study usedobservation, questionnaire, and interview methods to investigate the destruction of mangrove forestsecosystem and local community involvement in mangrove forests rehabilitation. The results showed thatthe region has suffered damage to the mangrove with a total density value of 626.67 trees/ha andmangrove forest cover in all types of <50%. The level of public participation was affected by socialstatus, planning, attitudes, and community rules in Teluk Belitung.Keywords: mangrove, community, participation, rehabilitation